1998
DOI: 10.1016/s0020-7292(98)00053-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial of nifedipine vs. ritodrine in threatened preterm labor

Abstract: Objecti¨es: To compare the tocolytic efficacy and maternal tolerance of nifedipine with ritodrine in the management of threatened preterm labor. Methods: Prospective randomized study of 52 singleton pregnancies with preterm labor between 26 and 34 week's gestation. The capacity to delay delivery 48 h, 7 days, until week 36 or until fetal weight reached 2500 g were the outcome variables assessed. Doppler ultrasound studies were performed on the fetal umbilical artery as control. Results: No significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 20 publications
2
30
1
2
Order By: Relevance
“…In another study, no difference was found in Doppler measurement parameters (PI and RI) in UA before and 3 hours after drug application (15). In our study, we did not find any significant difference in Doppler ultrasonography parameters for UA, UtA, and MCA before and 2 hours (early) after nifedipine treatment.…”
Section: Discussioncontrasting
confidence: 75%
“…In another study, no difference was found in Doppler measurement parameters (PI and RI) in UA before and 3 hours after drug application (15). In our study, we did not find any significant difference in Doppler ultrasonography parameters for UA, UtA, and MCA before and 2 hours (early) after nifedipine treatment.…”
Section: Discussioncontrasting
confidence: 75%
“…Various studies have compared ritodrine with nifedipine and found that both are equally effective in suppressing preterm labor but side effects were significantly less with nifedipine [8][9][10][11][12]. In our study also no significant difference was noted in maternal and neonatal side effects but less side effects were noted in nifedipine group.…”
Section: Discussionsupporting
confidence: 52%
“…564 The review of inhibition of threatened preterm labour with calcium channel blockers 565 included 12 RCTs. [566][567][568][569][570][571][572][573][574][575][576][577] Updating the searches retrieved a further five RCTs. [578][579][580][581][582] Further details of the review can be found in Appendix 6, Table 133.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…[566][567][568][569][571][572][573][574][575][578][579][580] Twelve studies excluded women with multiple gestations. [566][567][568][569]571,[574][575][576][577][578]580,581 Studies that included women with multiple gestations are denoted with an asterisk in the forest plots. 570,572,573,579,582 Data were available on the following outcomes: birth within 48 hours of intervention, birth within 7 days of intervention, spontaneous preterm birth before 37 weeks' gestation, spontaneous preterm birth before 34 weeks' gestation, perinatal mortality and admission to neonatal intensive care.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%